Peran Komunikasi Pelatih dalam Penguatan Kolaborasi Tim Futsal Mahasiswa - Sumbaha, Wahyu Asmaraman; Pribadi, Muhammad Adi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
This study aims to examine how the coach of the Futsal Student Activity Unit (UKM) at Universitas Tarumanagara applies communication strategies in building teamwork through the lens of Communication Accommodation Theory developed by Howard Giles. The study employs a qualitative approach using a phenomenological method. Data were collected through in-depth interviews with the coach as the primary informant, supported by relevant documentation and observational data. The findings indicate that the coach applies various forms of communication accommodation, particularly convergent accommodation, by adjusting language use, speaking style, and interpersonal approaches to suit the players’ diverse characteristics and backgrounds. The coach also demonstrates communicative equality among players, both senior and junior, which contributes to the development of team solidarity. In addition to verbal communication, the use of nonverbal cues and message repetition plays an important role in fostering a positive communication climate. These communication strategies significantly contribute to the formation of a team culture that emphasizes respect, openness, and discipline, thereby supporting the development of strong and cohesive teamwork. Penelitian ini bertujuan untuk mengetahui bagaimana pelatih Ukm Futsal Universitas Tarumanagara menerapkan strategi komunikasi dalam membangun kerjasama tim melalui pendekatan Teori Akomodasi Komunikasi yang dikembangkan oleh Howard Giles. Penelitian ini menggunakan pendekatan kualitatif dengan metode Fenomenologi. Data diperoleh melalui wawancara mendalam dengan pelatih sebagai narasumber utama. Hasil penelitian menunjukkan bahwa pelatih menerapkan berbagai bentuk akomodasi komunikasi terutama akomodasi konvergen, dengan menyesuaikan bahasa, gaya bicara, dan pendekatan personal sesuai dengan karakter dan latar belakang pemain. Pelatih juga menunjukkan kesetaraan komunikasi antar pemain baik senior maupun junior, untuk membentuk solidaritas tim. Selain komunikasi verbal, penggunaan komunikasi nonverbal dan pengulangan pesan juga menjadi bagian penting dalam menciptakan suasana komunikasi yang positif. Strategi komunikasi ini secara signifikan berkontribusi dalam membentuk budaya tim yang menjunjung nilai respek, keterbukaan, kedisiplinan sehingga mendukung terciptanya kerjasama tim yang solid.